Specificity of the Marketing Mix of Economic Higher Educational Institutions in Bulgaria - Ognyanov, Ognyan (Research Papers, 2025)
The report frames the elements of the "7P" model of the higher education marketing mix with specific real-world examples by each element. The purpose of the report is to describe the theoretical content of each of the seven elements of the specified model using a critical analysis and synthesis of existing scientific literature. The subject of the report is the marketing mix, and the object is the economic higher education institutions in Bulgaria.
Keywords: Marketing of higher education; Marketing mix; Students' attraction; Students' retention; Higher education institutions